Sensitivity Analysis for Seafloor Geodetic Constraints on Coseismic Slip and Interseismic Slip-Deficit Distributions - Murakami, Sota; Ichimura, Tsuyoshi; Fujita, Kohei; Hori, Takane; Ohta, Yusaku (Frontiers in Earth Science, 2021)
Estimating the coseismic slip distribution and interseismic slip-deficit distribution play an important role in understanding the mechanism of massive earthquakes and predicting the resulting damage. It is useful to observe the crustal deformation not only in the land area, but also directly above the seismogenic zone. Therefore, improvements in terms of measurement precision and increase in the number of observation points have been proposed in various forms of seafloor observation. However, there is lack of research on the quantitative evaluation of the estimation accuracy in cases where new crustal deformation observation points are available or when the precision of the observation methods have been improved. On the other hand, the crustal structure models are improving and finite element analysis using these highly detailed crustal structure models is becoming possible. As such, there is the real possibility of performing an inverted slip estimation with high accuracy via numerical experiments. In view of this, in this study, we proposed a method for quantitatively evaluating the improvement in the estimation accuracy of the coseismic slip distribution and the interseismic slip-deficit distribution in cases where new crustal deformation observation points are available or where the precision of the observation methods have been improved. As a demonstration, a quantitative evaluation was performed using an actual crustal structure model and observation point arrangement. For the target area, we selected the Kuril Trench off Tokachi and Nemuro, where M9-class earthquakes have been known to occur in the past and where the next imminent earthquake is anticipated. To appropriately handle the effects of the topography and plate boundary geometry, a highly detailed three-dimensional finite element model was constructed and Green's functions of crustal deformation were calculated with high accuracy. By performing many inversions via optimization using Green's functions, we statistically evaluated the effect of increase in the number of observation points of the seafloor crustal deformation measurement and the influence of measurement error, taking into consideration the diversity of measurement errors. As a result, it was demonstrated that the observation of seafloor crustal deformation near the trench axis plays an extremely important role in the estimation performance.